Do national health priorities align with Global Burden of Disease estimates on disease burden? An analysis of national health plans and official governmental websites - Oliveira, C. B. [UNESP]; Ferreira, G. E.; Buchbinder, R.; Machado, G. C.; Maher, C. G. (Elsevier, 2023)
Objective: To investigate the alignment of national health priorities with a country's burden of disease as measured by disability-adjusted life years (DALYs). Methods: We identified priorities in national health plans and the 20 most burdensome conditions measured by DALYs from the 2017 Global Burden of Disease Study. We computed point-biserial correlations (rpb) between DALYs and being nominated as a health priority and the pooled proportion (95% confidence intervals [CIs]) of the 20 most burdensome conditions nominated as a priority across countries. Results: We identified national health plans and official governmental websites in 145 countries. There was little to no correlation (rpb = 0.06, 95% CI: 0.02 to 0.09) between national DALY data and whether a condition was nominated as a health priority. The pooled proportion of the 20 most burdensome conditions nominated as priorities across countries was 46%. HIV/AIDS had the greatest number of nominations as a national health priority (62 countries) as well as the greatest match with the burden of disease (among the top 20 most burdensome conditions in 51 [82%] countries). Low back pain, headache disorders and congenital birth defects had the lowest proportion of nominations as health priorities in countries where they were in the top 20 most burdensome conditions (6%, 6% and 11%, respectively). Conclusion: Globally, there were low correlations between national health priorities and GBD estimates on disease burden. Failing to prioritise health priorities according to burden may mean that insufficient resources have been directed to improve health outcomes for people with those health conditions.
Keywords: Disease burden; Health policy; Health priority; National health planning